Features of the biomorphological and geographic structure of segetal floras in a number of regions in Russia - O. G. Baranova; A. S. Tretyakova; N. N. Luneva; A. A. Zverev; P. V. Kondratkov; T. A. Terekhina; G. R. Khasanova; S. M. Yamalov; M. V. Lebedeva; N. A. Bagrikova (Труды по прикладной ботанике, генетике и селекции)
Background. Biomorphological and geographic analyses conducted on long geographic gradients are relevant for identifying botanical and geographic features of segetal floras.Materials and methods. A comparative analysis was used to study biomorphological and geographic elements of segetal floras in nine regions of Russia: Vologda, Leningrad, Novgorod, Sverdlovsk and Rostov Provinces, the Republic of Bashkortostan, the Republic of Crimea, the Udmurt Republic, and Altai Territory.Results. Biomorphological groups in the compared segetal floras contained approximately equal ratios of therophytes and hemicryptophytes, monocarpic and polycarpic herbaceous plants. Meanwhile, the indigenous fraction manifested a higher share of polycarpic herbs (about 60–70%), while monocarpic herbs predominated in the alien fraction (80–90%). For the most part, indigenous plants represented widespread species (Holarctic and Eurasian), mainly plurizonal ones. At the same time, the composition of geographic elements in segetal floras retained the features of their locations. Species of southern distribution prevailed in the segetal flora of Crimea, while Central and East Asian species in Altai Territory. Depending on the zonal arrangement of segetal floras, the shares of boreal, forest-steppe and steppe species changed. The ratios among geographic elements in the alien fractions of the compared segetal floras were relatively stable. The groups of Eurasian and American species were the most numerous.Conclusion. The ratio of life forms (an increased share of therophytes, and a decreased share of phanerophytes) is probably a characteristic feature of the segetal flora, associated with the living environments of plants in agricultural phytocenoses. Geographic analysis confirmed that segetal floras retained their biogeographical features.